2019
DOI: 10.1155/2019/8581547
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Gastric Wall Thickening Detected in Abdominal CT Scan to Predict Gastric Malignancy

Abstract: Background Early diagnosis of gastric cancer is one of the most important parameters affecting the survival of the disease. In this study, we aimed to stress the importance of antrum wall thickness in CT examination. Method The study included 111 patients between ages of 18 and 95 who had antral wall thickening in computed tomography and also had endoscopic evaluation performed in the same clinic. The patients were divided into two groups as benign and malignant according to the pathology results. The thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…It is believed that GC enhancement peaks most often in the portal venous phase (17,18). In our current study, comprehensive assessment of the differentiation degree of GC by multiphase CECT improved the accuracy of GC diagnosis; similarly, the CT enhancement differences among GC with 3 different differentiation degrees were the largest in the portal venous phase, and the observation was easiest at the time of peak enhancement.…”
Section: Discussionsupporting
confidence: 56%
“…It is believed that GC enhancement peaks most often in the portal venous phase (17,18). In our current study, comprehensive assessment of the differentiation degree of GC by multiphase CECT improved the accuracy of GC diagnosis; similarly, the CT enhancement differences among GC with 3 different differentiation degrees were the largest in the portal venous phase, and the observation was easiest at the time of peak enhancement.…”
Section: Discussionsupporting
confidence: 56%
“…Certainly, MT in isolation poses a dilemma given the fact that some malignancies have been identified in asymptomatic patients [30]. It is this very cohort that poses the biggest clinical challenge.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports showing that elevated CAR levels were associated with aggressive tumor behavior and poor prognosis in oncology patients. [33][34][35] Qin et al [10] and Gibson et al [12] reported that high CAR values reflected the severity of infection in the acute phase of inflammatory bowel disease. Both studies showed that elevated CAR values were associated with the extent and severity of the infection.…”
Section: Discussionmentioning
confidence: 99%